2010
DOI: 10.1080/00288306.2010.526547
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoearthquake histories across a normal fault system in the southwest Taranaki Peninsula, New Zealand

Abstract: The tectonic origin, palaeoearthquake histories and slip rates during the last c. 26 ka have been examined for six normal faults (referred to here as the Rahotu, Oaonui, Kina, Ihaia, Kiri and Pihama faults) within the Taranaki Rift, New Zealand. A minimum of 13 ground-surface rupturing palaeoearthquakes have been recognised on four of the faults using analysis of displaced late Quaternary stratigraphy and landforms. These data, in combination with 21 new radiocarbon dates, constrain the timing, slip and magnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 50 publications
4
13
0
Order By: Relevance
“…This slow extension and shortening is related to slow clockwise rotation of the Manawatu block relative to the Wanganui block about a nearby pole (at ∼0.8°/Myr; Table 3). Similarly, the Wanganui block rotates relative to the Australian Plate about a nearby pole at ∼0.7°/Myr, leading to 1–2.5 mm/yr of shortening in the northwestern South Island and 1–2 mm/yr of extension near Cape Egmont in the North Island, a similar result to previous studies [ King and Thrasher , 1996; Wallace et al , 2004; Fraser et al , 2006; Giba et al , 2010; Townsend et al , 2010]. …”
Section: Joint Interpretation Of Gps and Geological Datasupporting
confidence: 89%
“…This slow extension and shortening is related to slow clockwise rotation of the Manawatu block relative to the Wanganui block about a nearby pole (at ∼0.8°/Myr; Table 3). Similarly, the Wanganui block rotates relative to the Australian Plate about a nearby pole at ∼0.7°/Myr, leading to 1–2.5 mm/yr of shortening in the northwestern South Island and 1–2 mm/yr of extension near Cape Egmont in the North Island, a similar result to previous studies [ King and Thrasher , 1996; Wallace et al , 2004; Fraser et al , 2006; Giba et al , 2010; Townsend et al , 2010]. …”
Section: Joint Interpretation Of Gps and Geological Datasupporting
confidence: 89%
“…In addition, kinematic analyses of normal fault outcrops along the northern Taranaki coast suggest NW-SE extension for the faults that were active between 0.3 and 5 Ma, which is consistent with regional fault strikes [Giba et al, 2010]. Townsend et al [2010] characterized the recurrence rate, timing, and magnitude of six active normal faults to the southwest of Mount Taranaki. These active faults show a regional NE-SW to ENE-WSW trend (varies between N35°E and N65°E) and indicate paleoseismicity with magnitudes of > 6 for these faults.…”
Section: Comparisons Between the Stress Pattern And Geological Data Isupporting
confidence: 60%
“…These active faults show a regional NE-SW to ENE-WSW trend (varies between N35°E and N65°E) and indicate paleoseismicity with magnitudes of > 6 for these faults. The tectonic or volcanic origin of these faults was discussed by Townsend et al [2010], and they suggested that the faults were formed due to tectonic activity because they were probably active before the volcanic activity. The consistency between our determined S Hmax orientation and the trend of these faults further supports a tectonic origin for these faults (Figure 7).…”
Section: Comparisons Between the Stress Pattern And Geological Data Imentioning
confidence: 99%
“…The faults in Table 1 range in SES from 0.5 to 16.9 m, with the lower bound defined by the detection limit of geological investigations of normal faults. In New Zealand, SES on individual faults may be approximately uniform (Van Dissen & Nicol 2009;Little et al 2010;Townsend et al 2010) or vary by up to a factor of five (Nicol et al , 2011bTownsend et al 2010; Figure 2). Whether most faults adhere to the quasi-uniform or variable SES models, and under what geological conditions each of these models applies, are important questions (e.g.…”
Section: Single-event Slipmentioning
confidence: 97%